Dynamic functional connectomics signatures for characterization and differentiation of PTSD patients. Issue 4 (14th May 2013) - Li, Xiang; Zhu, Dajiang; Jiang, Xi; Jin, Changfeng; Zhang, Xin; Guo, Lei; Zhang, Jing; Hu, Xiaoping; Li, Lingjiang; Liu, Tianming
<x xml:space="preserve">Abstract</x> Functional connectomes (FCs) have been recently shown to be powerful in characterizing brain conditions. However, many previous studies assumed temporal stationarity of FCs, while their temporal dynamics are rarely explored. Here, based on the structural connectomes constructed from diffusion tensor imaging data, FCs are derived from resting‐state fMRI (R‐fMRI) data and are then temporally divided into quasi‐stable segments via a sliding time window approach. After integrating and pooling over a large number of those temporally quasi‐stable FC segments from 44 post‐traumatic stress disorder (PTSD) patients and 51 healthy controls, common FC (CFC) patterns are derived via effective dictionary learning and sparse coding algorithms. It is found that there are 16 CFC patterns that are reproducible across healthy controls, and interestingly, two additional CFC patterns with altered connectivity patterns [termed signature FC (SFC) here] exist dominantly in PTSD subjects. These two SFC patterns alone can successfully differentiate 80% of PTSD subjects from healthy controls with only 2% false positive. Furthermore, the temporal transition dynamics of CFC patterns in PTSD subjects are substantially different from those in healthy controls. These results have been replicated in separate testing datasets, suggesting that dynamic functional connectomics signatures can effectively characterize and differentiate PTSD patients. Hum Brain Mapp 35:1761–1778, 2014. © 2013 Wiley Periodicals, Inc.